Diet of the Atlantic bonito Sarda sarda (Bloch, 1793) in the Northeast Aegean Sea. (27th March 2013) - Fletcher, N.; Batjakas, I. E.; Pierce, G. J.
Summary: Seasonal and size‐related patterns in feeding habits of the Atlantic bonito ( Sarda sarda ) in the Northeast Aegean were investigated over a 2‐year period May 2007 – May 2009 based on analysis of stomach contents of 134 fish ranging from 266–655 mm fork length. The fish were caught by purse‐seine boats operating around the islands of Lesvos and Chios (Greece). Of the stomachs examined, 46% contained at least one prey item and significant seasonal and size‐related patterns were found in the occurrence of non‐empty stomachs. The overall diet composition in terms of numerical importance was 71% fish, 28% crustaceans and 1% cephalopods. Of the fish, Engraulidae ( Engraulis encrasicolus ) were the dominant prey taxon, followed by Centracanthidae ( Spicara spp.) and then Clupeidae ( Sardina pilchardus ). Statistically significant monthly variation in diet was apparent, suggesting that S. sarda take advantage of seasonally abundant prey fish in the study area, but no size‐related variation in the importance of the main prey species was detected.